2020
DOI: 10.1093/conphys/coaa061
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive capacity in the foundation tree species Populus fremontii: implications for resilience to climate change and non-native species invasion in the American Southwest

Abstract: Populus fremontii (Fremont cottonwood) is recognized as one of the most important foundation tree species in the southwestern USA and northern Mexico because of its ability to structure communities across multiple trophic levels, drive ecosystem processes and influence biodiversity via genetic-based functional trait variation. However, the areal extent of P. fremontii cover has declined dramatically over the last century due to the effects of surface water diversions, non-native species invasions and more rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 111 publications
2
40
1
Order By: Relevance
“…These extreme temperatures can simultaneously damage the electron transport capacity of Photosystem II and increase photorespiration (Allakhverdiev et al, 2008;Hultine, Froend, et al, 2020;O'Sullivan et al, 2017). Therefore, warm-adapted trees likely prioritize maintaining midday leaf conductance to evaporatively cool the canopy (Fauset et al, 2018;Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020;Michaletz et al, 2015). The combination of these leaf morpho-physiological features allows SD trees to achieve higher levels of transpirational cooling of their leaves while reducing heat gain from incident light radiation (Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020).…”
Section: Adaptive Syndrome Trait Correlations Within the Sd Ecotypementioning
confidence: 99%
See 3 more Smart Citations
“…These extreme temperatures can simultaneously damage the electron transport capacity of Photosystem II and increase photorespiration (Allakhverdiev et al, 2008;Hultine, Froend, et al, 2020;O'Sullivan et al, 2017). Therefore, warm-adapted trees likely prioritize maintaining midday leaf conductance to evaporatively cool the canopy (Fauset et al, 2018;Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020;Michaletz et al, 2015). The combination of these leaf morpho-physiological features allows SD trees to achieve higher levels of transpirational cooling of their leaves while reducing heat gain from incident light radiation (Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020).…”
Section: Adaptive Syndrome Trait Correlations Within the Sd Ecotypementioning
confidence: 99%
“…Therefore, warm-adapted trees likely prioritize maintaining midday leaf conductance to evaporatively cool the canopy (Fauset et al, 2018;Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020;Michaletz et al, 2015). The combination of these leaf morpho-physiological features allows SD trees to achieve higher levels of transpirational cooling of their leaves while reducing heat gain from incident light radiation (Hultine, Allan, et al, 2020;Hultine, Froend, et al, 2020). For example, another recent study using genotypes from the same common garden as the present study reported that the SD ecotype trees displayed 35% higher midday leaf transpiration rates and 4°C lower leaf temperature than the MR ecotype trees (Hultine, Allan, et al, 2020).…”
Section: Adaptive Syndrome Trait Correlations Within the Sd Ecotypementioning
confidence: 99%
See 2 more Smart Citations
“…Accurately estimated tree canopy temperature can be used to detect tree populations and genotypes with different rates of transpiration and carbon sequestration, which can help identify trees that can better respond to increasing temperature, episodic heat waves, and prolonged drought conditions (Ludovisi et al, 2017). Tree canopy temperature reflects critical plant physiological processes, particularly transpiration and leaf carbon budgets (Gates, 1968; Hultine et al, 2020a,b; Santini et al, 2019). For example, on the warm edge of its distribution, the groundwater‐dependent, riparian Fremont cottonwood is exposed to some of the warmest mean annual temperatures in North America, often approaching 50 °C in mid‐summer (Cooper et al, 2019).…”
Section: Introductionmentioning
confidence: 99%